1966
DOI: 10.1115/1.3645963
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Damage and Effect of Mean Strain in Low-Cycle Fatigue of a 2024-T351 Aluminum Alloy

Abstract: By assuming a linear cumulative damage hypothesis for strain cycling, theories are developed in this paper for fatigue life under varying strain amplitude, residual ductility after a given history of strain cyling, and life under mean strain condition. These predictions are based on uniaxial completely reversed cycling behavior. The expressions obtained were compared with the experimental results on 2024-T351 aluminum alloy as well as other data available in the literature. The agreements between theories and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The sequence effects of Fig. 2 do not occur if all of the levels cause significant plastic straining (13)(14)(15)(16)(17), which is consistent with the observation that the initiation period is short in the low cycle region.…”
Section: Sequence Effectssupporting
confidence: 73%
“…The sequence effects of Fig. 2 do not occur if all of the levels cause significant plastic straining (13)(14)(15)(16)(17), which is consistent with the observation that the initiation period is short in the low cycle region.…”
Section: Sequence Effectssupporting
confidence: 73%
“…12 Some investigators have studied the effects of the strain ratio R for aluminium metals. 27,28 The experimental results showed that the compressive mean strain on lowcycle fatigue has the same effect as the tensile mean strain only if their magnitudes were the same. The following empirical relationship has been suggested by Ohji et al 28 between the total strain range ε and the number of cycles to failure N f , which accounts for the variation in the strain ratio R as follows:…”
Section: E F F E C T O F S T R a I N R A T I O ( R)mentioning
confidence: 99%
“…The experimental results showed that the compressive mean strain on low‐cycle fatigue has the same effect as the tensile mean strain only if their magnitudes were the same. The following empirical relationship has been suggested by Ohji et al 28 between the total strain range Δɛ and the number of cycles to failure N f , which accounts for the variation in the strain ratio R as follows: where, a = (−1/ c ); material constant equal to the negative reciprocal of the fatigue ductility exponent c . …”
Section: Effect Of Strain Ratio (R)mentioning
confidence: 99%
See 1 more Smart Citation
“…The need to track stress-strain around a hysteresis curve to determine mean stress is taken out of the picture, making the embedded process easier to implement. One such empirical relationship between total strain range, Δε, and cycles to failure is adopted herein [15]. This empirical relationship which accounts for mean strain instead of mean stress is written as ′ (2) where =…”
Section: Damage Accumulationmentioning
confidence: 99%